25 PciCall, emergency psychological assistance. (26th April 2019) - Martos Torrecilla, L; Lozano Castellanos, D; Santos del Río, I; Prieto Gómez, S; Huguet Cuadrado, E; Estupiña Puig, FJ; Larroy García, C
Abstract : Background: PsiCall is an emergency telematic psychological assistance service for students of the Universidad Complutense de Madrid, and arises to attend the psychosocial needs of this population. The goal is offering emergency psychological care, prevent and detect early mental health disorders, and referral to other resources. Method: Psicall is composed by 18 operators, supervised by experienced clinical psychologyst and/or emergencies staff; and there's also a coordinator and a director of the service. There is a call center with four teleoperation stations to carry out the assistance service, which operates from 7.30 a.m. to 23.30 a.m. from Monday to Thursday, and 24 hours during the weekends. The activity includes: Assistance: which is done by telephone, email or chat. General and specific intervention protocols have been developed for problems such as anxiety, depression, autolytic ideation, etc., based on evidence, which serve as a guide to attend people. There are also screening tools and decision trees. The phonecalls are attended first in triage to obtain sociodemographic data and the reason of consultation. After this, another operator performs the attention. Derivation is made when there's a need for it. Investigation: PsiCall collect the data of the users, in agreement with RGPD, for descriptive and efficacy studies of the psychological intervention. Teaching: operators recibe specific training in telematic psychological intervention to carry out a better assitance. Results: PsiCall has attended more than 800 students who present psychological and social emergencies since 2017. Conclusion: PsiCall is a pioneering telematic psychological assitance service in Spanish universities that contributes to improve student´s wellness at the Complutense University of Madrid. Conflict of interest: None. Funding: Universidad Complutense de Madrid.